Dynamical Properties of Nanostructured Josephson‐Junction Based on the Schwinger Quantum Action Analysis. Issue 12 (7th October 2019) - Choi, Jeong Ryeol
Abstract: Using the Schwinger action principle, Josephson‐junction dynamics for nanodevices have been investigated with emphasis on characterizing their quantum features. Starting from the time‐ordered Hamiltonian for the phase of the current which flows across the junction, the propagator, the wave functions, and the joint entropy, which are crucial for quantum analyses of the nano systems, are derived. It is shown that while the propagator and the wave functions vary depending on external driving forces, the joint entropy is not affected from such forces. Interestingly, the probability densities oscillate over time on account of the influence of the time‐varying supercurrent in the junction. It is confirmed that if external perturbations on the junction‐current are more complicated, the time behaviors of the probability densities become conspicuously irregular. The properties of the joint entropy are also analyzed in detail. Due to damping of the system, the phase(ϕ) component of the joint entropy decreases linearly over time, whereas the conjugate momentum( q ) component exhibits linear increase; however, the corresponding joint entropy consequently does not vary. It is demonstrated that the joint entropy obeys the quantum minimum principle, and that there is a close relationship between the joint entropy and the uncertainty relation. Abstract : For implementing Josephson junctions in nanodevices that are expected to be widely used in next‐generation nanotechnologies, the characterization of quantum features associated with the junctions is important. Given this, quantum characteristics of the Josephson junction in nanostructured devices are analyzed by taking advantage of the elegant theory of Schwinger quantum action principle.